The movement of pre-adapted cool taxa in north-central Amazonia during the last glacial - D'Apolito, Carlos; Absy, Maria Lúcia; Latrubesse, Edgardo Manuel (Quaternary Science Reviews, 2017)
The effects of climate change on the lowland vegetation of Amazonia during the last glacial cycle are partially known for the middle and late Pleniglacial intervals (late MIS 3, 59–24 ka and MIS 2, 24–11 ka), but are still unclear for older stages of the last glacial and during the last interglacial. It is known that a more seasonal dry-wet climate caused marginal forest retraction and together with cooling rearranged forest composition to some extent. This is observed in pollen records across Amazonia depicting presence of taxa at glacial times in localities where they do not live presently. The understanding of taxa migration is hindered by the lack of continuous interglacial-glacial lowland records. We present new data from a known locality in NW Amazonia (Six Lakes Hill), showing a vegetation record that probably started during MIS 5 (130–71 ka) and lasted until the onset of the Holocene. The vegetation record unravels a novel pattern in tree taxa migration: (1) from the beginning of this cycle Podocarpus and Myrsine are recorded and (2) only later do Hedyosmum and Alnus appear. The latter group is largely restricted to montane biomes or more distant locations outside Amazonia, whereas the first is found in lowlands close to the study site on sandy soils. These findings imply that Podocarpus and Myrsine responded to environmental changes equally and this reflects their concomitant niche use in NW Amazonia. Temperature drop is not discarded as a trigger of internal forest composition change, but its effects are clearer later in the Pleniglacial rather than the Early Glacial. Therefore early climatic/environmental changes had a first order effect on vegetation that invoke alternative explanations. We claim last glacial climate-induced modifications on forest composition favoured the expansion of geomorphologic-soil related processes that initiated forest rearrangement. © 2017 Elsevier Ltd
Keywords: Climate Change; Forestry; Plants (botany); Vegetation; Amazonia; Glacial; Plant Migration; Pollen; Vegetation Structure; Glacial Geology; Angiosperm; Biome; Climate Change; Coniferous Tree; Environmental Change; Forest Ecosystem; Glacial-interglacial Cycle; Holocene; Last Glacial; Paleoclimate; Plant; Pollen; Vegetation Cover; Vegetation Structure; Amazonia; Alnus; Hedyosmum; Myrsine; Podocarpus